Comparative Study of Physicochemical and Technological Characteristics in Some White and Yellow Corn Hybrids - Zahrat El-Ola, M. Mohamed; Azza, A. Omran (Food Technology Research Journal)
This study aimed to assess the quality characteristics of two white corn hybrids SC131, and TWC 321, and three yellow corn hybrids: SC176, SC181, and TWC354. The impact of those hybrids in tortillas processing were investigated. The white corn hybrid SC131 had the largest significant thousand kernel weight. The flour of yellow corn hybrids considerably contained more protein, fats, ash, crude fiber, and total carotenoids content than white corn whole meal. White corn had more total carbohydrates and amylose. Yellow corn whole meal had greater levels of potassium, zinc, iron, and phosphorus. Protein digestibility value was higher in yellow corn than white corn hybrids. The yellowness values of the yellow corn tortillas were greater than white corn tortillas. All tortilla samples prepared with white and yellow corn flour had high overall acceptability scores, with SC131 being the most acceptable hybrid, followed by SC181. These results could be useful in identifying the suitable corn hybrids with required nutrients content, toward targeting specific industrial uses and accordingly recommending its cultivation in breeding programs.